The use of propaganda in Malaysiakini online news pertaining to Polis DiRaja Malaysia (PDRM) / Annuar Amri Abdul Muluf and Noor Nirwandy Mat Noordin - Abdul Muluf, Annuar Amri; Mat Noordin, Noor Nirwandy (CMIWS and UiTM Press, 2014)
Online news has become a newly favoured option among the current society for it suits the fast paced lifestyle nowadays. The latest development in any news around the world can be retrieved anywhere and anytime by just a single click. Malaysiakini as one of the most popular online news portal in our country which capitalises on this opportunity by publishing interesting news and stories including those involving provocative and sensitive issues that have indeed created an overwhelming pattern of response amongst its readers.